THE 3 HOURS-HYDROTHERMAL SYNTHESIS OF HIGH SURFACE AREA SUPERPARAMAGNETIC Fe3O4 CORE-SHELL NANOPARTICLES - Esty Octiana Sari; Ahmad Fadli; Amun Amri (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
The monodisperse core-shell Fe3O4 nanoparticles have been successfully synthesized by short times (3 hours) hydrothermal method at 220oC from FeCl3, citrate, urea and PEG. The as-synthesized samples have been characterized using X-ray diffraction (XRD), Transmission Electron Mycroscopy (TEM), Bruneur-Emmet-Teller (BET) surface area analyzer, and Vibrating Sample Magnetometer (VSM). The XRD result showed the as-shinthesized products were pure Fe3O4. The TEM image showed the magnetite nanoparticles have monodisperse core-shell shape. The BET result showed the magnetite nanoparticles have 650.757 m2/g surface area. The hysteresis curve showed the magnetite nanoparticles exhibit superparamagnetic properties. This simple method obtained 60 nm core-shell Fe3O4 particles with superparamagnetic, high surface area as well as hydrophylic properties. Those properties are promising for various biomedical application. The advantages of simple and short times methods with high quality of product make this method very promising to be applied.